If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2(11 + -4x) = 82 + x 5x + (11 * 2 + -4x * 2) = 82 + x 5x + (22 + -8x) = 82 + x Reorder the terms: 22 + 5x + -8x = 82 + x Combine like terms: 5x + -8x = -3x 22 + -3x = 82 + x Solving 22 + -3x = 82 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 22 + -3x + -1x = 82 + x + -1x Combine like terms: -3x + -1x = -4x 22 + -4x = 82 + x + -1x Combine like terms: x + -1x = 0 22 + -4x = 82 + 0 22 + -4x = 82 Add '-22' to each side of the equation. 22 + -22 + -4x = 82 + -22 Combine like terms: 22 + -22 = 0 0 + -4x = 82 + -22 -4x = 82 + -22 Combine like terms: 82 + -22 = 60 -4x = 60 Divide each side by '-4'. x = -15 Simplifying x = -15
| 3(2p+7)=15(p+-4) | | 9(m-2)=m+40 | | 0.14-0.01(x+2)=-0.03(4-x) | | 10b+-25+-3b=4b-1 | | 11d=81+-16d | | -7a+-10=20+-3a | | 5(2n-5)=(8n+4)+9 | | 7x-3=5(x+1)+2x-8 | | 0.9x-3.8=0.7 | | 2(3x-6)=18 | | 3(3x-6)=18 | | 23x-6=18 | | 3(4x-2)=12x | | 3(2x+11)=6x+33 | | 8y+3(y-6)=3(y+2)-5 | | -5(t-2)+8t=5t-1 | | 3n+16=7n | | 12(n+3)=3(12+4n) | | 0.06(y-6)+0.08y=0.04y-0.09(10) | | 0.06(y-6)+0.08=0.04y-0.09(10) | | 8+5n=8.5 | | 40-5x=90 | | 2x=(15-3x) | | 0.30x+0.15(20)=0.15(112) | | 2x=15-3x | | 9x=18+3x | | 1+2y=4 | | 0+2y=4 | | -1+2y=4 | | 6x=4x+4 | | 4x=3x+11 | | -2+2y=4 |